2019
DOI: 10.1182/blood-2019-127514
|View full text |Cite
|
Sign up to set email alerts
|

Dose Optimization in Elderly CML Patients Treated with Bosutinib after Intolerance or Failure of First-Line Tyrosine Kinase Inhibitors

Abstract: Background and Rationale. Bosutinib (BOS), dasatinib (DAS) and nilotinib (NIL) are 2nd generation TKIs with similar second-line efficacy. The use of DAS and NIL may be burdened by pulmonary, infectious, cardiovascular and metabolic complications; these complications are more frequent and more clinically relevant in the elderly. BOS could represent an important therapeutic option in elderly patients intolerant to or failing a first-line TKI, but the dose of 500 mg OAD may be higher than necessary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Intolerance was the most frequent reason of permanent discontinuation, while no progression was observed. These results showed that in elderly patients second-line bosutinib may be highly effective and better tolerated at a daily dose lower than 500 mg, namely at 300 mg/day [31].…”
Section: Bosutinibmentioning
confidence: 84%
“…Intolerance was the most frequent reason of permanent discontinuation, while no progression was observed. These results showed that in elderly patients second-line bosutinib may be highly effective and better tolerated at a daily dose lower than 500 mg, namely at 300 mg/day [31].…”
Section: Bosutinibmentioning
confidence: 84%
“…Overall, 60% of the cohort achieved MR3 by 12 months, while 38 and 19% achieved MR4 and MR4.5, respectively. 47…”
Section: Methodsmentioning
confidence: 99%
“…For the elderly patients, the choice of salvage TKI after failing frontline therapy becomes even more difficult as the comorbidities have to be taken into account as major concerns of safety include cardiovascular toxicities and effusions in major organs. A small phase 2 study of bosutinib from Italian group suggested the gradual dose wrap-up of bosutinib could be an option for elderly CML patients (≥60 yr old) after failure of frontline TKI (imatinib 83%, dasatinib 11% and nilotinib 6^) [ 24 ]. The study was designed to start bosutinib 200 mg for 2 weeks, then to increase 300 mg.…”
Section: Tyrosine Kinase Inhibitors After Failure Of Frontline Therap...mentioning
confidence: 99%
“…The rate of MMR by 12 months among patients with resistance was 52% and 65% with intolerance. After median follow-up of 9 months, 51 of 63 patients remained on bosutinib [ 24 ]. A multicenter, retrospective analysis reported the outcome of salvage dasatinib for elderly CML-CP (>60 yr old) patients intolerant/resistant to imatinib [ 25 ].…”
Section: Tyrosine Kinase Inhibitors After Failure Of Frontline Therap...mentioning
confidence: 99%